Perspectives of immigrant parents on education for newly arrived adolescents in Iceland - Julia Zacharova Galinudóttir 1979-; Maureen Sarah Mc Laughlin 1980- (2018)
The study explores how immigrant parents in Iceland, perceive school collaboration and reception departments for their adolescent children, who at the time of arrival entered lower secondary school. Parent-teacher collaboration and school services are elements that can help immigrant students succeed academically. For the research, we used a case study method. Data collected from the interviews were interpreted using qualitative analysis. Four participants were interviewed, and data was collected using questions regarding parent-school collaboration and services that are offered for the newly arrived students. The results of the study showed that parents mainly focus on the wellbeing of their children and have positive attitudes towards the educational system in Iceland. The findings of the parental collaboration with the school revealed that parents are willing to participate in their children's school activities, but language is a barrier for many school activities. The findings of the reception department showed that immigrant students mainly make friends with other immigrant students and in one case the language of communication and instruction was primarily in English. The findings revealed that the reception department program is an exclusory practice that separates immigrant children from the mainstream class, inhibiting integration with the Icelandic peers.